Educational tourism in Malaysia: implications for community development practice - Abu Samah, Asnarulkhadi; Ahmadian, Maryam (Canadian Center of Science and Education, 2013)
Background: This paper aims to discuss the impacts of educational tourism on the residents in the Klang Valley, Malaysia. Educational tourism is a means to empower educational communities, host communities, local entrepreneurs, and to enhance economic prosperity. Method: A cross-sectional survey was carried out in five districts in Selangor and Kuala Lumpur (Federal Territory) which are located in the Klang Valley, and Nilai, Negeri Sembilan. Data was collected from 700 respondents using structured questionnaire from the Klang Valley and Nilai. Results: Pearson correlation analysis revealed that, there is significant positive moderate relationship between attitude, environmental impact, economic impact, and socio-cultural impact and practice. Multiple linear regressions showed that socio-cultural and economic impact of educational tourism, and local community attitude has significantly contributed to residents’ practice to educational tourists in the Klang Valley. Conclusion: The findings propose new insights into the socio-cultural and economic impacts of educational tourism and community development practice. Educational tourism can sustain the development of career paths for workers and local communities. The results of this study present practical information on sustainable educational programs for both the Ministry of Higher Education and the Ministry of Tourism.